Biosynthesis of iron nanoparticles by sulphate reducing bacteria and its application in remediating chromium from water - KIRTI RANJAN DAS; SAVITA KERKAR (International Journal of Pharma and Bio Sciences, 2017)
Chromium is an industrially important metal, extensively used in metal plating, tanning, pigment and refractory industries; hence its discharge in to the environment is unavoidable. Due to its persistence, toxicity, bioaccumulation property it has become a threat to living organisms. Present study deals with isolation of a hypersaline sulphate reducing bacteria (SRB) strain WCA1 from Ribandar saltpan, Goa, India which produced Iron sulfide nanoparticle and studied for Cr remediation from water.The SRB isolate was closely related to Desulfotomacculum acetoxidans by biochemical and 16S rRNA gene sequence analysis. The SRB synthesizes iron sulfide nanoparticles in the growth media when supplied with 0.5M FeSO4.7H2O. From SEM-EDS and XRD results, the nanoparticles were characterized to be iron sulfide nanoparticle of 21nm size. These nanoparticles were found effective in Cr remediation from water. The maximum adsorption of Cr by the nanoparticle was achieved within 2 hours of reaction time. The optimum nanoparticle concentration for maximum removal was determined to be 0.25g.L-1. The efficiency of Cr remediation increases in acidic conditions.Ca-Alginate immobilized iron sulfide nanoparticle beads had an advantage over its bare form in terms of low mobility, less self-aggregation and easy separation from a solution. The bead form increased the overall Cr remediation capacity of nanoparticle and it contributed to 99% of Cr removal from the water.